Specification and analytical evaluation of heterogeneous dynamic quorum-based data replication schemes - Storm, Christian (Vieweg+Teubner Verlag, 2012)
Data replication by employing quorum systems is an important concept to improve operation availability on data objects in distributed systems that have strong data consistency demands. These data replication schemes must be modeled and carefully evaluated with respect to different quality measures. Christian Storm addresses the former by a uniform data replication scheme specification method and realizes the latter by a comprehensive approach to the analytical evaluation of quorum-based data replication schemes. The system model allows to evaluate operation availability and other quality measures for the write as well as for the read operation.